Design Of Score Administration Program For Lecturer In Universitas Muhammadiyah Surakarta Based On Single Application Page - Inayati, Iin Silviya, Bana Handaga, S.T.,M.T.,P.h.D (2016)
Administrasi Nilai Universitas Muhammadiyah Surakarta(ANUMS) has been applied by Local Area Network (desktop-based). Along with the changing of times, the system is lacking in some respects. So, a new ideas for changing the system becoming a web-based from desktop-based. Web technology used Single Page Application (SPA). SPA is a new breakthrough concept of application that has one page. Application of SPA in ANUMS system compiled with the latest Web technologies such as Javascript, HTML and framework basedJavascript that AngularJS. The result from these studies produced an ANUMS application based on website with SPA that is use to input and manage the student's score that is better to increase the performance of services of the ANUMS system based on desktop application.Based on testing the system performance is done by using Black box to observe the execution of results through the test data and the functional check of the software. Based on testing of feasibility of the system using questionnaires ANUMS can be concluded that the application of the SPA on ANUMS system can handled and succsessfull to reach the system goal.